Life cycle analysis of gasification and Fischer-Tropsch conversion of municipal solid waste for transportation fuel production. (1st January 2023) - Lee, Uisung; Cai, Hao; Ou, Longwen; Benavides, Pahola Thathiana; Wang, Yixuan; Wang, Michael
Abstract: Non-recyclable municipal solid waste (MSW) can be used as feedstock for liquid fuel production via gasification followed by Fischer-Tropsch (FT) processes. Given the heterogeneity of MSW material composition and variation in material properties, its convertibility to liquid hydrocarbon fuels could vary widely, affecting the sustainability of utilizing non-recyclable MSW for fuel production. This study evaluates the life cycle greenhouse gas (GHG) emissions (carbon intensities [CIs]) of FT fuels from non-recyclable MSW. Key issues that could greatly affect the CIs were examined, including fossil carbon content of the MSW, emission implications of diverting non-recyclable MSW from landfills to fuel production, and conversion efficiency. Results show that the CIs of fuels produced from various waste streams range 80–105 gCO2 e/MJ, which may exceed the CI of petroleum fuels. Higher fossil carbon content in the MSW feedstock tends to incur higher GHG emissions as biogenic carbon emissions are considered carbon neutral. Meanwhile, diverting different fractions of non-recyclable MSW, such as food waste and low-quality paper, from landfills may result in GHG emissions that may include the potential avoidance of methane emissions and potential sequestration of biogenic carbon that is foregone. To reduce GHG emissions, a carbon capture and sequestration option in the fuel production stage is considered, which could reduce the CI by 53–64 gCO2 e/MJ. Carbon fates of different non-recyclable MSW in landfills are further evaluated to determine how they vary and impact the CIs of MSW-derived fuels. Highlights: Evaluated carbon intensities of liquid fuels produced from municipal solid waste. Considered the impact of avoided business-as-usual (BAU) landfill cases. Waste-derived fuels may not present emission reduction compared to fossil fuels. Fossil carbon emissions and avoided BAU contribute to the carbon intensities. Carbon capture and sequestration reduces the carbon intensity of MSW-derived fuels.